2018
DOI: 10.1029/2018gl078104
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis and Resilience of the AMOC in an Eddy‐Permitting GCM

Abstract: We show a quasi‐irreversible shutdown (hysteresis) of the Atlantic meridional overturning circulation (AMOC) in an unfluxadjusted global climate model with an eddy‐permitting ocean. This global climate model is a prototype of one submitted to the sixth Coupled Model Intercomparison Project and is the most comprehensive model to show this behavior. The AMOC has a resilience timescale for a given hosing: If the hosing exceeds the critical hosing for collapse for only a limited time, the AMOC recovers when the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 48 publications
4
84
0
Order By: Relevance
“…However, flux adjustments should be applied with caution: Dijkstra and Neelin () showed how the flux correction procedure, as applied by, for instance, Manabe and Stouffer (), could artificially affect the stability of the AMOC in models; the flux‐corrected configuration could have multiple equilibria in a regime where the non‐flux‐corrected configuration would have a single equilibrium. That multiple equilibria can also be found in models that do not have flux adjustments have been shown in more recent studies (Hawkins et al, ; Hu et al, ; Jackson & Wood, , ; Mecking et al, ).…”
Section: Multiple Equilibria Of Amoc In a Hierarchy Of Modelsmentioning
confidence: 58%
See 4 more Smart Citations
“…However, flux adjustments should be applied with caution: Dijkstra and Neelin () showed how the flux correction procedure, as applied by, for instance, Manabe and Stouffer (), could artificially affect the stability of the AMOC in models; the flux‐corrected configuration could have multiple equilibria in a regime where the non‐flux‐corrected configuration would have a single equilibrium. That multiple equilibria can also be found in models that do not have flux adjustments have been shown in more recent studies (Hawkins et al, ; Hu et al, ; Jackson & Wood, , ; Mecking et al, ).…”
Section: Multiple Equilibria Of Amoc In a Hierarchy Of Modelsmentioning
confidence: 58%
“…Mecking et al () showed that freshwater convergence within the North Atlantic is an important feedback for opposing the salinification caused by the ITCZ shift discussed in the previous section. Jackson and Wood (, ) also discuss this feedback in different experiments with the same GCM, showing that both collapsed and recovering AMOC states after hosing feature an increasing salinity in the subtropical gyre and decreasing salinity in the subpolar gyre. In both states the basin‐integrated salinity is quite similar.…”
Section: Feedbacks Controlling Amoc Stabilitymentioning
confidence: 94%
See 3 more Smart Citations